2017
DOI: 10.1124/jpet.117.240630
|View full text |Cite
|
Sign up to set email alerts
|

Mashiningan Improves Opioid-Induced Constipation in Rats by Activating Cystic Fibrosis Transmembrane Conductance Regulator Chloride Channel

Abstract: Opioid receptor stimulants are analgesics used in patients with and without cancer; however, they often cause constipation, resulting in poor adherence and deterioration of the quality of life. Hence, suitable treatments for constipation are required. In this study, we investigated the pharmacological mechanisms of action of mashiningan (MNG), a Kampo medicine used to treat constipation, and evaluated the effect of MNG on opioid-induced constipation in rats. MNG (100 or 300 mg/kg) was orally administered to no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…These alterations of fecal properties have been used as indicators of constipation symptoms and as indices of therapeutic effects against constipation [ 40 ]. Therefore, improvements of discharged fecal parameters, including increases of stool numbers and soften stools, and intestinal transit time, is one of the important strategy for the constipation treatment [ 41 , 42 ]. Previous studies showed dramatically decreased the stool-related parameters, including stool numbers, weights and water contents in lop-treated rats [ 12 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…These alterations of fecal properties have been used as indicators of constipation symptoms and as indices of therapeutic effects against constipation [ 40 ]. Therefore, improvements of discharged fecal parameters, including increases of stool numbers and soften stools, and intestinal transit time, is one of the important strategy for the constipation treatment [ 41 , 42 ]. Previous studies showed dramatically decreased the stool-related parameters, including stool numbers, weights and water contents in lop-treated rats [ 12 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…A flavonoid, genistein, which is a known potent PTK inhibitor, can PTK-independently activate CFTR from the extracellular (not intracellular) side (French et al, 1997;Wang et al, 1998;Zhou et al, 1998;Niisato et al, 1999). CFTR was also activated by some herbs such as menthol (Morise et al, 2010), which is a cyclic terpene alcohol produced by the peppermint herb; mashiningan (Harada et al, 2017), which is a Japanese herbal (Kampo) medicine used to treat constipation; as well as Junchoto, another Kampo medicine empirically prescribed for chronic constipation (Numata et al, 2018).…”
mentioning
confidence: 99%
“…Indeed, the evidence supportive of these observations has been briefly described: oral administration of JCT (300 or 1000 mg/kg) greatly improves opioid-induced severe constipation in a rat model with increased fecal count and dried fecal weight [ 9 ]. A similar CFTR-targeted improvement of constipation has been investigated in detail in a rat model treated with another Kampo medicine, Mashiningan, although in this case stimulation of cGMP-mediated signaling was presumed to be responsible for CFTR activation [ 10 ]. However, again, whether CFTR is involved here was not unequivocally proved because of the considerably higher concentration of the drug used to selectively inhibit CFTR (CFTR-inhbitor-172, 20 μM).…”
Section: Discussionmentioning
confidence: 99%
“…JCT and MNG are prescribed exclusively for elderly patients suffering from spastic constipation, which results mostly in softened stool. Recently, it was suggested that such laxative actions of JCT and MNG may involve CFTR activation [ 9 , 10 ]. However, this speculation relies entirely on the presumptive specificity of an organic CFTR inhibitor used (CFTRinh-172) which also inhibits other types of Cl − channels including volume-sensitive anion channels [ 11 ] and ClC-2 [ 12 ] at micromolar concentrations, thus lacking rigorous proof at the molecular level.…”
Section: Introductionmentioning
confidence: 99%